Sociodemographic Risk, Developmental Competence, and PTSD Symptoms in Young Children Exposed to Interpersonal Trauma in Early Life - Enlow, Michelle Bosquet (2013)
Children under age six years are disproportionately exposed to interpersonal trauma, including maltreatment and witnessing intimate partner violence (IPV), and may be particularly susceptible to negative sequelae. However, young children have generally been neglected from trauma research; thus, little is known about the factors influencing vulnerability to traumatic stress responses and other negative outcomes in early life. This study examined associations among interpersonal trauma exposure, sociodemographic risk, developmental competence, and posttraumatic stress disorder (PTSD) symptoms in 200 children assessed prospectively from birth to 1(st) grade via home and laboratory observations, record reviews, and maternal and teacher interviews. Greater trauma exposure and sociodemographic risk and lower developmental competence predicted more severe PTSD symptoms. Developmental competence partially mediated the association between exposures and symptoms. Trauma exposure fully mediated the association between sociodemographic risk and symptoms. Neither sociodemographic risk nor developmental competence moderated trauma exposure effects on symptoms. The findings suggest that (a) exposure to maltreatment and IPV has additive effects on posttraumatic stress risk in early life, (b) associations between sociodemographic adversity and poor mental health may be attributable to increased trauma exposure in disadvantaged populations, and (c) early exposures have a negative cascade effect on developmental competence and child mental health.